The Hippo pathway regulates stem cell proliferation, self-renewal, and differentiation. - Liu, H.; Jiang, D.; Chi, F.; Zhao, B. (Protein & Cell, 2012)
Stem cells and progenitor cells are the cells of origin for multi-cellular organisms and organs. They play key roles during development and their dysregulation gives rise to human diseases such as cancer. The recent development of induced pluripotent stem cell (iPSC) technology which converts somatic cells to stem-like cells holds great promise for regenerative medicine. Nevertheless, the understanding of proliferation, differentiation, and self-renewal of stem cells and organ-specific progenitor cells is far from clear. Recently, the Hippo pathway was demonstrated to play important roles in these processes. The Hippo pathway is a newly established signaling pathway with critical functions in limiting organ size and suppressing tumorigenesis. This pathway was first found to inhibit cell proliferation and promote apoptosis, therefore regulating cell number and organ size in both Drosophila and mammals. However, in several organs, disturbance of the pathway leads to specific expansion of the progenitor cell compartment and manipulation of the pathway in embryonic stem cells strongly affects their self-renewal and differentiation. In this review, we summarize current observations on roles of the Hippo pathway in different types of stem cells and discuss how these findings changed our view on the Hippo pathway in organ development and tumorigenesis.